Do Index Funds Monitor?. (23rd February 2021) - Heath, Davidson; Macciocchi, Daniele; Michaely, Roni; Ringgenberg, Matthew C
Abstract: Passively managed index funds now hold over 30% of U.S. equity fund assets; this shift raises fundamental questions about monitoring and governance. We show that, relative to active funds, index funds are less effective monitors: (a) they are less likely to vote against firm management on contentious governance issues; (b) there is no evidence they engage effectively publicly or privately; and (c) they promote less board independence and worse pay-performance sensitivity at their portfolio companies. Overall, the rise of index funds decreases the alignment of incentives between beneficial owners and firm management and shifts control from investors to managers.